The Democratic Ambivalence of EU Disintegration: A Mapping of Costs and Benefits. Issue 3 (5th May 2021) - Patberg, Markus
Abstract: Since Brexit, there has been increasing interest in democratic theory in the question of the conditions under which reversals of European integration can be considered legitimate. So far, however, the literature is very much focused on the specific case of the United Kingdom's withdrawal from the European Union. In this article, I seek to prepare the ground for a systematic theory that clarifies, at a general level, the scope and limits as well as the actors and procedures of democratically legitimate disintegration. To that end, I map the potential democratic costs and benefits of EU disintegration. In doing so, I distinguish five types of disintegration: retreat, revocation, exit, expulsion, and dissolution. All of these measures can produce conflicts between the democratic claims of citizens and peoples. Many of these cannot be resolved but must be dealt with politically. Overall, disintegration bears more potential costs for citizens than for peoples. Zusammenfassung: Seit dem Brexit gibt es in der Demokratietheorie ein zunehmendes Interesse an der Frage, unter welchen Bedingungen Umkehrungen der europäischen Integration als legitim gelten können. Bislang konzentriert sich die Literatur allerdings stark auf den spezifischen Fall des Austritts des Vereinigten Königreichs aus der Europäischen Union. In diesem Artikel geht es mir darum, den Boden für eine systematische Theorie zu bereiten, die auf einer allgemeinen Ebene den Umfang und die Grenzen sowie die Akteure und Verfahren demokratisch legitimer Desintegration bestimmt. Zu diesem Zweck identifiziere ich die demokratischen Kosten und Vorteile, die EU‐Desintegration potenziell mit sich bringt. Dabei unterscheide ich fünf Typen von Desintegration: Rückzug, Rücknahme, Austritt, Ausschluss und Auflösung. Alle diese Maßnahmen können zu Konflikten zwischen den demokratischen Ansprüchen von Bürgern und Völkern führen. Diese können häufig nicht gelöst werden, sondern müssen politisch bearbeitet werden. Insgesamt birgt Desintegration mehr potenzielle Kosten für Bürger als für Völker. Résumé: Depuis Brexit, la question des conditions dans lesquelles l'intégration européenne peut être légitimement inversée gagne un intérêt croissant en théorie de la démocratie. Cependant, la littérature existante se concentre surtout sur le cas spécifique du retrait du Royaume‐Uni de l'Union Européenne. Dans cet article, je pose les bases d'une théorie systématique de la désintégration démocratique qui clarifie, à un niveau général, sa portée, ses limites, ainsi que les acteurs et les procédures qui peuvent la rendre légitime. J'identifie les coûts et bénéfices démocratiques potentiels de la désintégration de l'UE et distingue cinq types de désintégration : le retrait, la révocation, la sortie, l'expulsion et la dissolution. Toutes ces mesures peuvent générer des conflits entre les revendications démocratiques des citoyens et des peuples. S'ils ne peuvent être résolus, ils doivent être traités politiquement. Dans l'ensemble, la désintégration a un coût potentiellement plus élevé pour les citoyens que pour les peuples.